Haemolymp parameters of Penaeus monodon (Giant black tiger shrimp) infected with white spot syndrome virus (WSSV). - Go, Princess Joy G. (2004.)
Hemolymph parameters were used as an indicator for Penaeus monodon, giant black tiger shrimp, immunology and condition. Hemolymph was obtained by a puncture on the ventral part of the hemocoel. Total hemocyte count was used to measure the immune response indices of P. monodon. The total hemocyte count of the infected shrimp was lower compared to PBS (control) infected shrimp. Differential hemocyte count was used to characterize which cell was mainly infected with white spot syndrome virus (WSSV). The result of this study confirmed earlier observation that the targets of WSSV infection were granular cells and semigranular cells. Phenoloxidase (PO) activity has been considered as a potential marker for cellular parameter. Infected shrimp showed a higher production of melanin and antimicrobial compounds to PBS injected shrimps. In regards to humoral parameter, concentration of plasma protein can be considered as criteria for health status. An increase of plasma protein concentration was observed in WSSV infected shrimp.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Penaeus monodon -- Infected; Shrimps, Giant Black Tiger; White Spot Syndrom Virus (WSSV) -- Shrimp